(untitled) (Journal of Pharmaceutical Negative Results, 2020)
Objective:This study aimed to compare the effectiveness of ultrasound-guided and fluoroscopy-guided percutaneous nephrolithotomy (PCNL) in terms of stone-free rates and blood loss, as well as secondary outcomes such as operative time, hospital stay, and complication rates.Methods:One hundred patients with renal stones scheduled for PCNL were divided into two groups. Group A (50) underwent ultrasound-guided PCNL, while Group B (50) underwent fluoroscopy-guided PCNL. The same surgeon performed all procedures in the prone position, using 30 Fr Amplatz sheaths for access. Doppler ultrasound was employed in Group A to minimize vascular injury.Results:Stone-free rate was 80 percent in Group A (ultrasound) and 90 percent in Group B (fluoroscopy), slightly better for fluoroscopy. Mean blood loss was less in Group A (250± 80 mL) than in Group B (310 90 mL). Moreover, there was no decline in hemoglobin either in the ultrasound-guided (1.2 ±0.4 g/dL) or the fluoroscopy group (1.5 ± 0.5 g/dL). A patient in Group A and two in Group B needed blood transfusions. Secondary results showed a shorter operative time for Group B (70 ±10 minutes) than for Group A (85± 12 minutes). Meanwhile, the hospital stay was similar for each group (2.2± 0.6 days for ultrasound; 2.1 ± 0.5 days for fluoroscopy). Complication rates were similar: 6 cases (12%) of Grade I/II complications per group in Group A and 7 cases (14%) in Group B.Conclusion:Ultrasound- and fluoroscopy-based PCNL are viable treatments for renal stones, but they have different strengths. Ultrasound-guided blood loss and hemoglobin loss were minimized, while fluoroscopy guided a slightly higher stone-free rate and shorter operative time. Given similar safety profiles, ultrasound-guided PCNL might be an alternative to fluoroscopy if eliminating radiation and bleeding offsets the benefits.